PRODUCTIVITY, DISTRIBUTION SYSTEMS, AND MARKETING PROFITABILITY OF GREEN BEANS IN WEOE VILLAGE, WEWIKU DISTRICT, MALAKA - Maria Gabriela Asela; Damianus Adar; Maria Bano (Buletin Ilmiah Impas, 2026)
Mung bean (Vigna radiata L.) farming is a food commodity that plays a crucial role as a source of vegetable protein and a source of income for farmers in rural areas. In Weoe Village, Wewiku District, Malaka Regency, mung beans have been cultivated for generations, but their development still faces various obstacles, such as low productivity, an inefficient marketing distribution system, and suboptimal marketing profitability. This study aims to determine the productivity level of mung bean farming, analyze the marketing distribution system, and determine the level of marketing profitability of mung bean in Weoe Village, Wewiku District, Malaka Regency. This research was conducted in Weoe Village, Wewiku District, Malaka Regency from September to October 2025. The research method used was descriptive quantitative with a survey technique. Respondents were selected using simple random sampling of 60 mung bean farmers. The data used consisted of primary and secondary data obtained through observation, interviews, documentation, and literature review. Data analysis was conducted using productivity analysis, marketing margin analysis, farmer's share, marketing efficiency, marketing profitability, and Revenue Cost Ratio (R/C Ratio) analysis. The results show that mung bean farming productivity in Weoe Village is still relatively low and varies among farmers. The mung bean marketing distribution system involves several marketing institutions, including village collectors, sub-district retailers, district retailers, and wholesalers, resulting in a long marketing chain and relatively high marketing margins. The farmer's share received by farmers was 66.6%, indicating that farmers can still increase their share of the price through improvements to shorter and more efficient marketing channels. Overall, the mung bean marketing business remains profitable and viable, but marketing efficiency needs to be improved to sustainably increase the income and welfare of mung bean farmers.